Julgamento de adolescentes sobre pessoas fumantes e não fumantes - Simão, Paula Vanessa Pestana [UNESP]; Caramaschi, Sandro [UNESP] (My University, 2011)
The addiction to the habit of smoking is a main worry to health experts and educators, mainly with respect to adolescents. However, few studies are conducted with the purpose of investigating how the teenagers themselves see and judge people who smoke. In this work, the perception of adolescent high school students of unknown smokers and nonsmokers was investigated. The sample constituted of 100 students (50 male and 50 female) aged from 16 to 21 years old. The data were collected by presenting photographs of models (a man and a woman) in two versions: holding a cigarette or not. The attribution of characteristics was accomplished through an instrument specifically elaborated for this research, through scores on bipolar scales of 15 characteristics. An analysis of data allowed us to verify that, in general, people without a cigarette were more favorably judged in 86% of the characteristics investigated. Data also showed some differences between male and female judgments of models with or without a cigarette concerning the following characteristics: constructiveness, health, niceness, loyalty, calmness, optimism, discretion, reliability, humility and wisdom. This research allowed us to verify the opinion of teenagers about the appearance of smokers, which could contribute to directing the efforts towards smoking control more efficiently.

A adesão ao hábito de fumar vem preocupando especialistas em saúde e educadores, principalmente no que diz respeito a adolescentes. Entretanto, poucos estudos se dedicam a investigar a perspectiva dos próprios jovens acerca das pessoas que fumam. Neste estudo, a percepção de adolescentes alunos do ensino médio sobre pessoas desconhecidas fumantes e não fumantes foi investigada. A amostra foi constituída de 100 alunos (50 do sexo masculino e 50 do feminino) com idades entre 16 e 21 anos. A coleta de dados foi feita mediante apresentação de fotos de modelos (um homem e uma mulher) em duas versões: com cigarro e sem cigarro na mão. A atribuição de características foi feita por meio de um instrumento especificamente construído para esta pesquisa, a partir da pontuação em escalas bipolares de 15 características. A análise dos dados nos permitiu constatar que, de uma forma geral, as pessoas sem cigarro são julgadas de maneira mais favorável em 86% das características investigadas. Foram verificadas algumas diferenças na forma como homens e mulheres atribuem valores aos modelos com e sem cigarro nas características construtividade, saúde, "legal", lealdade, calma, otimismo, discrição, confiabilidade, humildade e sabedoria. Os dados permitem verificar a opinião de jovens a respeito da aparência de pessoas fumantes, podendo-se dessa forma direcionar esforços mais eficientes ao controle do tabagismo.
Teenagers’ judgment of unknown smokers and nonsmokers
Keywords: Adolescents; Smoking; Behavior; Perception; Adolescente; Tabagismo; Comportamento; Percepção